Improving quality of cassava peel meal as raw material for tilapia feed - Putra, Achmad Noerkhaerin; Indayah, Unah; Nokiyah, Nokiyah; Syamsunarno, Mas Bayu (Depik, 2022)
Cassava peel meal (CPM) has potential as a raw material for fish feed due to its abundant availability and good nutritional content. The high crude fiber content inhibits the use of CPM as a raw material for fish feed. Therefore, this study aims to evaluate the effect of Aspergillus niger fermentation of CPM on dietary nutrient digestibility and growth performance of tilapia (Oreochromis niloticus). It was conducted in 2 stages. The first stage was a fermentation process of CPM, which used a factorial randomized design consisting of a dose difference of A. niger, namely 10, 15, 20, 30 g.kg-1 and a fermentation time of 0, 12, 24 hours with 3 replications each. At a dose of 1.5% of A. niger during 24 hours of fermentation, the crude fiber content of fermented CPM was reduced up to 7.19%. the second stage was a 45 days feeding trial on tilapia used a completely randomized design consisting of 3 different treatments with 3 replications, namely: reference feed, unfermented cassava peal meal based diet (CPMD), and A. niger fermented CPMD. A. niger fermented CPMD showed an increase in growth, dry matter, protein, energy, and raw material digestibility, as well as daily growth rate compared to unfermented CPMD. The daily growth rate of fermented CPMD of 1.32%/day was significantly higher with P0.05 than the unfermented CPMD of 0.72%/day. Furthermore, the digestibility value of material test in the fermented CPMD (48.73%) was significantly higher (P0.05) than unfermented CPMD (11.74%). These results indicate that A. niger fermented CPM has the potential to be used as raw material for tilapia fish feed.Keywords:Aspergillus nigerFermentationTilapiaCrude fiber